EDUCATIONAL POLICIES OF THE EUROPEAN UNION - BETWEEN THE PAST AND THE FUTURE - Cristina-Iulia Gîlă (Romanian Journal of Historical Studies)
The presented article aims to summarize the preoccupations of the European institutions on the issue of education in the European Union from the first Communities to the present. This study looks at the evolution of economic growth from an economy in a profound process of transformation to a Europe tailored to the challenges of the future where education, training and youth occupy a significant role in Europe 2025. The paper also covers the tools and the programs proposed by the European Union in order to achieve a common area of education. The article also addresses the question of what action is needed at European level for the future of young people and to what extent European educational cooperation programs meet needs and solutions to global issues. European Union documents demonstrate the importance of achieving the objectives of the Europe 2020 strategy for the idea of collaboration and cooperation between schools, online platforms, the creation of a network across Europe, and the promotion of volunteering and non-formal activities